Elder law : evolving European perspectives - Numhauser-Henning, Ann, 1951- (Edward Elgar Publishing, 2017)
Population ageing poses a huge challenge to law and society, carrying important structural and institutional implications. This book portrays elder law as an emerging research discipline in the European setting in terms of both conceptual and theoretical perspectives as well as elements of the law. Providing a deepened understanding of population ageing in terms of vulnerability, intergenerational conflict and solidarity, expert contributors highlight the necessity for a contextualized ageing concept. As well as offering a comparative analysis of active ageing policies across the EU, this book examines a range of topics including age discrimination in employment and the freedom of movement of EU citizens from the ageing individual's point of view. It also goes on to describe elder care developments, discussing the ageing individual's autonomy in relation to both traditional inheritance rights and growing instances of dementia. Timely and engaging, this book will appeal to academic scholars and students in relevant areas of law as well as those studying across the social sciences. Exploring a broad range of socio-legal issues in relation to demographic ageing, it will also inform legal practitioners and policymakers alike.